2018
DOI: 10.1155/2018/8216578
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Secretory Receptor for Advanced Glycation End Products Protects Endothelial Cells from AGEs Induced Apoptosis

Abstract: Endogenous secretory receptor for advanced glycation end products (esRAGE) binds extracellular RAGE ligands and blocks RAGE activation on the cell surface, protecting endothelial cell function. However, the underlying mechanism remains unclear. Endothelial cells overexpressing the esRAGE gene were generated using a lentiviral vector. Then, quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to assess esRAGE mRNA and protein levels, respectively. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…However, a recent study that made use of a Quantitative Real Time Polymerase Chain Reaction (RT-PCR) and western blot assay provided an insight as they showed that esRAGE abrogates AGEs- mediated apoptosis and inflammation in endothelial cells by downregulating the expressions of the proapoptotic marker-Bax and inflammatory marker NF-κB while upregulating the expression of the antiapoptotic markerBcl-2 (Guomin et al, 2018).…”
Section: Esrage and Srage As Biomarkers For Rage-mediated Metabolic Ementioning
confidence: 99%
“…However, a recent study that made use of a Quantitative Real Time Polymerase Chain Reaction (RT-PCR) and western blot assay provided an insight as they showed that esRAGE abrogates AGEs- mediated apoptosis and inflammation in endothelial cells by downregulating the expressions of the proapoptotic marker-Bax and inflammatory marker NF-κB while upregulating the expression of the antiapoptotic markerBcl-2 (Guomin et al, 2018).…”
Section: Esrage and Srage As Biomarkers For Rage-mediated Metabolic Ementioning
confidence: 99%
“…Zhu et al [ 42 ] studied chicken breast and found that protein and lipid oxidation could promote AGEs formation. At the same time, endogenous AGEs are synthesized in animals, and reducing sugars in meat react spontaneously with the amino acid residues of proteins, lipids, and nucleic acids to form AGEs at a later stage [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…RAGE receptors are associated with the cell membrane of most body cells and can combine with various ligands, including AGE, amphoterin, β-amyloid, S100/calgranulin [108][109][110][111][112], which results in the activation of proinflammatory pathways that play an important role in the etiopathogenesis of schizophrenia. esRAGE subtype (endogenous secretory RAGE) is an unbound form of the RAGE receptor that protects cells from the harmful effects of AGE in the mechanism of blocking RAGE activation [113]. Reduced levels of esRAGE are observed in schizophrenic patients, which consequently causes increased exposure to carbonyl stress [114].…”
Section: Glycation and Oxidative Damage In Schizophreniamentioning
confidence: 99%